Antibacterial activities of coumarin-3-carboxylic acid against Acidovorax citrulli - Zhu, Fa-Di; Fu, Xin; Ye, Huo-Chun; Ding, Hai-Xin; Gu, Liu-Shuang; Zhang, Jing; Guo, Yong-Xia; Feng, Gang (Frontiers in Microbiology, 2023)
Coumarin-3-carboxylic acid (3-CCA), previously screened from natural coumarins, was found to possess strong antibacterial activity against Acidovorax citrulli (Ac). In order to further evaluate the activity of this compound against plant bacterial pathogens and explore its potential value as a bactericidal lead compound, the activity of 3-CCA against 14 plant pathogenic bacteria in vitro and in vivo was tested. Results showed that 3-CCA exhibited strong in vitro activities against Ac, Ralstonia solanacearum, Xanthomonas axonopodis pv. manihotis, X. oryzae pv. oryzae, and Dickeya zeae with EC50 values ranging from 26.64 μg/mL to 40.73 μg/mL. Pot experiment results showed that 3-CCA had powerful protective and curative effects against Ac. In addition, the protective efficiency of 3-CCA was almost equivalent to that of thiodiazole copper at the same concentration. The results of SEM and TEM observation and conductivity tests showed that 3-CCA disrupted the integrity of the cell membrane and inhibited polar flagella growth. Furthermore, 3-CCA resulted in reductions in motility and extracellular exopolysaccharide (EPS) production of Ac while inhibiting the biofilm formation of Ac. These findings indicate that 3-CCA could be a promising natural lead compound against plant bacterial pathogens to explore novel antibacterial agents.